Trip generation modelling of Lipa City - Aloc, Dominic S.; Amar, Jan Aaron C.; Vergel, Karl B. N. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
This study aimed to create models for the first of the four-step model of travel demand forecasting - that is, trip generation. Lipa City, which is a first class component city in the province of Batangas and is composed of 72 barangays or zones, is the study area considered. Household Interview Surveys is conducted by the Office of Transportation Cooperatives and the results are encoded in a database. Two modelling techniques are used, namely: (1) regression analysis; and (2) trip rate method. For the regression analysis, fifteen (15) independent variables and two (2) dependent variables (i.e. , trips produced and trips attracted) are considered by trip purpose. Eight (8) trip purposes were identified: To Home; To Work; To School; To Private Business; To Employer's Business; To Medical; To Shopping; and To Church. Results of regression analysis showed that the population per zone, number of households per zone, workers per zone, students per zone and household head monthly income per zone are significant parameters for a particular zone to produce and attract trips. For the trip rate method, cross-classification tables are made for each purpose. Different household characteristics are cross-classified for each purpose (i.e., household size and household income for purpose 'To Home', or household income and occupation for purpose 'To Work'.) Results of the trip rate method illustrated the trip generation rates from different trip purposes.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Trip generation -- Mathematical models; Trip generation -- Philippines -- Lipa City